Admission circulating monocytes level is an independent predictor of outcome in traumatic brain injury. (21st March 2018) - Li, Zhiqi; Wu, Xing; Wu, Xuehai; Yu, Jian; Yuan, Qiang; Du, Zhuoying; Hu, Jin
ABSTRACT: Objective : The aim of this study was to assess the prognostic value of admission immune cell levels in the peripheral blood in determining outcomes in patients with TBI. Method : We studied 141 adult patients with mild-to-severe TBI (Glasgow Coma Scale (GCS) 3–15). Patient outcome was assessed using the Extended Glasgow Outcome Scale (GOSE) at 6 months post-injury. The area under the curve (AUC) was used to evaluate the predictive ability of immune cell levels. Uni- and multivariate analyses were performed to assess the independent predictors of 6-month outcome. Results : We found that admission monocyte count was not only a better predictor (AUC = 0.778; 95% confidence interval (CI), 0.679–0.858) of favourable outcomes (GOSE 5–8) at 6 months post-injury than were admission haemoglobin (AUC = 0.629; 95% CI, 0.522–0.728) and blood glucose (AUC = 0.616; 95% CI, 0.508–0.716) levels for patients with moderate-to-severe TBI (GCS ≤ 12), but also an independent predictor of 6-month outcome (adjusted odds ratio, 1.35; 95% CI, 1.10–1.65; p  = 0.004). Conclusions : The present study suggests that an increase in admission monocyte count is correlated with a favourable 6-month outcome in patients with moderate-to-severe TBI.